2012
DOI: 10.1111/j.1582-4934.2012.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of mouse TTF‐2 gene causes cleft palate

Abstract: In humans, mutations of the gene encoding for thyroid transcription factor-2 (TTF-2 or FOXE1) result in Bamforth syndrome. Bamforth syndrome is characterized by agenesis, cleft palate, spiky hair and choanal atresia. TTF-2 null mice (TTF-2−/−) also exhibit cleft palate, suggesting its involvement in the palatogenesis. However, the molecular pathology and genetic regulation by TTF2 remain largely unknown. In the present study, the recombinant expression vector pBROAD3-TTF-2 containing the promoter of the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Unfortunately, the thyroid phenotype of these mice was either not studied or not reported (personal communication from the authors) (21). Nevertheless, the findings in this mouse model support our observation of impaired palate and thyroid development in a patient with a FOXE1 gain-of-function mutation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Unfortunately, the thyroid phenotype of these mice was either not studied or not reported (personal communication from the authors) (21). Nevertheless, the findings in this mouse model support our observation of impaired palate and thyroid development in a patient with a FOXE1 gain-of-function mutation.…”
Section: Discussionsupporting
confidence: 71%
“…Cleft palate has been reported in both Foxe1 null mice and mice with Foxe1 overexpression (7,21). Unfortunately, the thyroid phenotype of these mice was either not studied or not reported (personal communication from the authors) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even if the patient presents features typical of Bamforth-Lazarus syndrome, functional studies show that FOXE1 mutated protein enhances transcriptional activity of both TG and TPO promoters. 187 This finding seems consistent with the observation that both Foxe1 null 69 and Foxe1 overexpressing mice 188 present cleft palate, one of the hallmark signs of Bamforth-Lazarus syndrome. The thyroid phenotype associated with FOEX1 mutations ranges from athyreosis to severe hypoplasia.…”
Section: Thyroid-enriched Transcription Factors and Thyroid Dysgenesissupporting
confidence: 80%
“…Animal experiments also support the conclusion that thyroid transcription factor-2 (TTF-2 or FOXE1) in knockout mice leads to abnormal development of the lip and palate, which suggests that overexpression of TTF-2 during palatogenesis may contribute to formation of a cleft palate. 17,18 This gives us enough confidence to think that FOXE1 is of decisive importance in cleft lip and palate and cleft palate alone in humans.…”
Section: Discussionmentioning
confidence: 92%
“…14,15 The FOXE1 transcription factor belongs to the forkhead family of transcription factors, and many studies have shown that it is a major genetic determinant for thyroid disease because it is the centre of a regulatory network of transcription factors and cofactors that initiate thyroid differentiation. [17][18][19][20][21] Similarly, when the median nasal prominence combines with the maxillary process or palatogenesis FOXE1 has an important role. Animal experiments also support the conclusion that thyroid transcription factor-2 (TTF-2 or FOXE1) in knockout mice leads to abnormal development of the lip and palate, which suggests that overexpression of TTF-2 during palatogenesis may contribute to formation of a cleft palate.…”
Section: Discussionmentioning
confidence: 99%